Genetic dissection of end‐use quality traits in two widely adapted wheat cultivars 'TAM 111' and 'TAM 112'. Issue 3 (29th April 2021) - Dhakal, Smit; Liu, Xiaoxiao; Girard, Audrey; Chu, Chenggen; Yang, Yan; Wang, Shichen; Xue, Qingwu; Rudd, Jackie C.; Ibrahim, Amir M. H.; Awika, Joseph M.; Johnson, Charles D.; Jessup, Kirk E.; et al.
Abstract: Quantitative trait loci (QTL) analysis genetically dissects complex traits, discerns their genetic control and genotype‐by‐environment interactions, and ultimately helps marker development for assisted breeding selection. A mapping population of 124 F5:7 recombinant inbred lines (RILs) derived from the cross of 'TAM 112' × 'TAM 111' was grown under seven diverse environments and evaluated for end‐use quality traits including kernel, flour, and dough‐mixing characteristics. The objective of this study was to detect QTL associated with end‐use quality traits in these two cultivars. Through 5, 948 single nucleotide polymorphisms (SNPs), 39 QTL regions were consistently identified in two or more environments or QTL analyses. Thirteen QTL regions associated to two or more traits were also identified. Among them, 11 QTL regions were in common on chromosomes 1A, 1B, 1D, 2D, and 4D associated to kernel hardness (HARD), kernel diameter (DIAM), single kernel weight (SKW), flour yield (FYLD), midline peak time (MLPT) with logarithm of odds (LOD) up to 42.0, and explained up to 49.3% of the phenotypic variation. Notably, Glu‐D1 loci at 414.3 Mb on chromosome 1D strongly influenced dough rheology and explained up to 54.6% of the trait variation for MLPT, with the favorable allele derived from TAM 112. Novel QTL for HARD, FYLD, and ASH were also identified on the chromosome 1A and 2A, 6B, and 7D, respectively. This study confirmed previously identified loci at major genes, some newly identified QTL on chromosomes, and the favorable alleles carried forward for improved end‐use quality. Core Ideas: One hundred twenty‐four RILs were characterized for 11 end‐use quality traits QTL were analyzed cross individual and mega environments to dissect epistasis and G × E A total of 39 consistent QTL on 11 chromosomes were identified Thirteen pleiotropic QTL on 6 chromosomes were determined Four common QTL with epistasis and epistasis × environment interactions have LOD > 10